HUBUNGAN MOTIVASI DAN PEKERJAAN IBU DENGAN PEMBERIAN MAKANAN PENDAMPING AIR SUSU IBU (MP-ASI) DINI PADA BAYI DI BAWAH USIA 6 BULAN - Pandu Sandika; Nur Afrinis; Emdas Yahya (Universitas Pahlawan, 2021)
Complementary feeding of breastmilk to infants aged less than 6 months can cause health problems such as constipation, diarrhea and allergies. It will have an impact on the nutritional status of the infant. The purpose of this study was to determine the relationship between motivation and mother occupation with complementary feeding of breastmilk to infants under the age of 6 months in Naga Beralih village the work area of Community Health centre Kampar Utara in 2020. This type of research was analytic with cross sectional design. The population of this research was mothers who have infants aged 0-6 months in Naga Beralih village, the working area of Community Health centre Kampar Utara, totaling 41 people. Data collection tools in this study used a questionnaire. Data analysis in this study used univariate and bivariate analysis with chi square. The results showed that most of the respondents have high motivation in giving complementary breastfeeding, most of the respondents work, most of the respondents give complementary foods to infant under the age of 6 months. There was a relationship of motivation with complementary feeding with p value of 0.001. There was a work relationship with the provision of complementary feeding under the age of 6 months in Naga Beralih village the work area of Community Health centre Kampar Utara in 2020 with a p value of 0.002. For health workers, in order to increase education about the importance of complementary breastfeeding by forming classes for infants and toddlers to provide information and demonstrations, especially regarding the amount of complementary breastfeeding, types of food and timing of complementary feeding.